Politics as a Vocation: Aung San Suu Kyi, Politician or Activist? - Myat, Mon Mon (Archīum Ateneo, 2019)
Myanmar’s opposition leader, Aung San Suu Kyi was seen by the world as a heroic activist and a Nobel Peace Laureate for nonviolent struggle. Since she became a stateswoman, the world’s opinion seemingly changed. In the context of the 2017 Rohingya crisis, she was even labeled an “ignoble laureate” by the New Yorker due to what the West perceived as her silence on the flight of more than 700,000 refugees from Western Myanmar to Bangladesh. This led Western opinion leaders to question her moral conviction and her iconic status as a human rights activist. Through Max Weber’s definion of a politican in his “Politics as a Vocation,” this paper examines whether Aung San Suu Kyi is a politician or an activist.